1991
DOI: 10.1159/000186375
|View full text |Cite
|
Sign up to set email alerts
|

Total and Split Renal Function Assessed by Ultrasound Doppler Techniques

Abstract: We evaluated total and split renal functions from the pattern for renal arterial blood flow detected by ultrasound Doppler in healthy subjects and patients with varying degrees of renal function and disorders other than renovascular hypertension or severe aortic valvular disease. A renal-time pulsed ultrasonic echo-Doppler device at 2.5 MHz was used with a translumbar approach. The ratio of peak diastolic (D) to systolic (S) velocity correlated well with both p-aminohippurate clearance and creatinine clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…Taken together with previous findings showing that the RI and PI reflect the vascular resistance peripheral to the measuring site [7,[13][14][15], the effects of dopamine on the RI and PI in the present study can thus be attributed to a lowered vascular resistance. Although the RI and PI appear to be equally meaningful indices, changes in the RVR correlated strongly with those in the PI, which may be more suitable for the evaluation of renovascular resis tance.…”
Section: Discussionsupporting
confidence: 89%
“…Taken together with previous findings showing that the RI and PI reflect the vascular resistance peripheral to the measuring site [7,[13][14][15], the effects of dopamine on the RI and PI in the present study can thus be attributed to a lowered vascular resistance. Although the RI and PI appear to be equally meaningful indices, changes in the RVR correlated strongly with those in the PI, which may be more suitable for the evaluation of renovascular resis tance.…”
Section: Discussionsupporting
confidence: 89%
“…The diagnostic validity of Doppler US in renal parenchymal disease is still under debate; however, recent studies have shown that the resistive index (RI) correlates with tubulointerstitial and vascular lesions [2]. Doppler US may also be used to evaluate orbital vascular flow velocities and characteristics [3].…”
Section: Introductionmentioning
confidence: 99%
“…These measurements, easily obtained in the transplanted kidney for its eterotopic position in the iliac fossa, can also be performed in the native kidneys [30] in the study of intraand extraparenchymal renal vascular problems and of any type of a spontaneous form of renal disease. …”
Section: Discussionmentioning
confidence: 99%
“…A third factor of caution in the interpretation of Doppler results is the increase in RI and PI along with the elevation in creatinine plasma levels or with the reduction in the nephrotic mass [26,29,30], The physiological significance of this fact is obscure, but must be taken into account when the data obtained from patients with reduced renal function are to be interpreted. For a correct interpretation of Doppler records, it is therefore necessary to know creatinine plasma levels.…”
Section: Recording Doppler Sonogramsmentioning
confidence: 99%